PENGARUH PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SINAR SOSRO - Kromei Lindania Aritonang; Nira Fadilah; Tomy Alexander Aritonang; Okta Viany Saragih (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2019)
Job satisfaction is an emotional state that is pleasant or unpleasant for employees to view their work. Factors that influence job satisfaction are career development and physical work environment. Career development is a staffing activity that helps employees plan for future careers so that the company and employees concerned can develop themselves to the maximum. The work environment is all that is around the worker who influences himself in carrying out the tasks charged. Unmet job satisfaction is due to unclear career development and an unfavorable work environment. PT. Sinar Sosro is engaged in the manufacture of beverages. The research method uses a quantitative approach, the type of research used is quantitative descriptive. Data collection is done by interviews, questionnaires and documentation studies. Data analysis used is a multiple linear regression. The population is all employees of 150 people, where 110 people as samples. The results showed that career development and physical work environment simultaneously and partially had a positive and significant effect on employee job satisfaction.